Análisis del comportamiento de un servidor de VOIP sobre una red de comunicación 5H. - Palma Gamarra, Leonardo Adrián (2022)
This case study deals with the analysis and behavior of a VoIP server on 5G communication networks and that means that the technology of the 4G network is lagging behind, although the network 5G is relatively new, people can't help but imagine what life would be like with that network. The 5G network is here to increase the speed of thing as we know them. Networks can meet the communication needs of billions of connected devices where you have the right combinación of speed, latency and cost the qualitative metodología since it uses existing information that can be found posted on the web, maratones, books, and pdf. Which we are using to base ourselves and be able to give it a corresponding conclusion. They is also talk of VoIP, which is based on the technology that allows the connection of conversations over the Internet or a computer network where calls are made be telephone software called VoIP all people with this technology can make calls from anywhere in the World as Long as they are connected to the Internet. Finally, it is possible to conclude that the 5G communications network improves the VoIP servers since, thanks to it, the bandidos is increased, thus giving the greatest transmission of information it also had greater spectral efficiency, better latancy, etc. Thus improving the VoIP servers and putting them to the maximum without the need to force them or require a lot of wok.